PENGARUH GOOD CORPORATE GOVERNANCE (GCG), PERTUMBUHAN PENJUALAN DAN CAPITAL INTENSITY TERHADAP FINANCIAL DISTRESS - Nur Kemala; Suripto Suripto (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the influence of Good Corporate Governance (GCG), Sales Growth and Capital Intensity on Financial Distress. The population of this study is the Food & Beverage companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023 as many as 82 companies. The sampling method in this study used purposive sampling so that obtained 43 companies with a study period of 5 (five) years reffering to annual reports from 2019-2023. The data analysis method used is panel data regression, regression model selection, classical assumption test, coefficient of determination test, F test and t test, processed using the help of the Eviews 12 application. The results of study explain that simultaneously all independent variables have no effect on financial distress. Partially shows that Good Corporate Governance (GCG) have no effect financial distress, sales growth has no effect on financial distress and capital intensity has no effect on financial distress